Exercise metabolism - Spriet, Lawrence L.; Hargreaves, Mark 1961- (Champaign, IL Human Kinetics, 2006)
Exercise Metabolism, Second Edition, provides a systematic, in-depth examination of the regulation of metabolic processes during exercise. Exercise physiologists, exercise biochemists, and biochemists will find this book a comprehensive reference, using the up-to-date information and the nearly 1,000 references in their own research and writing. In addition, graduate students in these disciplines can learn firsthand about the various regulations of metabolic processes during exercise as they prepare for careers in exercise physiology or biochemistry. Written by internationally recognized researchers, Exercise Metabolism, Second Edition, is both revised and expanded while retaining the essential elements of the first edition. It delves into the mobilization and utilization of substrates--glucose, lipid, and protein--during physical activity, and it explores metabolic factors in fatigue and metabolic adaptations to endurance training. Chapter 1 provides an overview of exercise metabolism. Metabolism during high-intensity exercise and the transition from rest to exercise are covered in chapter 2, which details the so-called anaerobic energy pathways. Chapter 3 discusses the effects of exercise on carbohydrate metabolism in skeletal muscle, while chapter 4 provides an overview of the important metabolic functions of the liver during exercise. Chapter 5 is a new chapter that addresses lactate transport in skeletal muscle, given the increased understanding of this topic since the first edition was published. Chapters 6 and 7 summarize the effects of exercise on lipolysis in adipose tissue and lipid metabolism in skeletal muscle, respectively. The contribution of protein and amino acids to exercise metabolism is discussed in chapter 8. Finally, metabolic factors in fatigue and the metabolic adaptations to endurance training are reviewed in chapters 9 and 10, respectively. Chapter-ending summaries help to condense the information and facilitate understanding. Exercise Metabolism, Second Edition, is a valuable reference to exercise physiologists, exercise biochemists, and biochemists, and it serves as an ideal text for graduate students in these disciplines.
Chapter 1. Overview of Exercise Metabolism / Lawrence L. Spriet, PhD, and Mark Hargreaves, PhD ; Metabolic Fuels and Rates of ATP Production ; Control of Metabolic Pathways ; Signals Matching ATP Synthesis and ATP Demand -- Chapter 2. Anaerobic Metabolism During Exercise / Lawrence L. Spriet, PhD ; Skeletal Muscle ATP Concentration Is Defended During Exercise ; Importance of Anaerobic Metabolism ; Sources of Anaerobic ATP ; Regulation of Anaerobic Energy Provision ; Carbohydrate ; Phosphocreatine ; Intermittent High-Intensity Exercise ; Anaerobic Metabolism at the Onset of Exercise ; Summary -- Chapter 3. Skeletal Muscle Carbohydrate Metabolism During Exercise ; Mark Hargreaves, PhD ; Muscle Glycogenolysis and Glucose Uptake During Exercise ; Regulation of Muscle Glycogenolysis ; Regulation of Muscle Glucose Uptake ; Regulation of CHO Oxidation ; Lactate Metabolism ; Postexercise CHO Metabolism ; Summary -- Chapter 4. Hepatic Metabolism During Exercise / Michael Kjær, MD ; Hepatic Glucose Output During Exercise: Glycogenolysis and Gluconeogenesis ; Feedback Regulation of Hepatic Glucose Output ; Feed-Forward Regulation of Hepatic Glucose Output ; Regulatory Hormonal and Neural Mechanisms in Hepatic Glucose Production ; Hepatic Uptake of Gluconeogenic Precursors ; Summary -- Chapter 5. Skeletal Muscle Lactate Transport and Transporters / Arend Bonen, PhD ; Lactate Transport System ; Lactate Transport Proteins ; MCT1 and MCT4 in Human Skeletal Muscle ; Subcellular Distribution of MCT1 and MCT4 in Muscle ; MCT1 and MCT4 Transporters and Lactate Transport ; Effects of Training on MCT1 and MCT4 ; Possible Roles of MCTs ; Summary -- Chapter 6. Adipose Tissue Lipid Mobilization During Exercise / Jeffrey F. Horowitz, PhD ; Regulation of Lipolysis in Adipose Tissue ; Regional Lipolysis ; Measuring Lipolysis in Vivo ; Regulation of Adipose Tissue Blood Flow ; Other Triglyceride Sources ; Lipolytic Response During Endurance Exercise ; Endurance Exercise Training ; Summary -- Chapter 7. Skeletal Muscle Lipid Metabolism During Exercise / Lorraine P. Turcotte, PhD ; Plasma Long-Chain Fatty Acid Metabolism ; Muscle Triacylglycerol Metabolism ; Plasma Triacylglycerol Metabolism ; Summary -- Chapter 8. Effect of Exercise on Skeletal Muscle Protein and Amino Acid Metabolism in Humans / Martin J. Gibala, PhD ; Protein Turnover and Exercise ; Skeletal Muscle Amino Acid Metabolism During Exercise ; Influence of Protein or Amino Acid Ingestion on Muscle Adaptation During Recovery ; Summary -- Chapter 9. Metabolic Factors in Fatigue / Kent Sahlin, PhD ; Limits of Energetic Processes ; Central Fatigue ; Peripheral Fatigue ; Integrated View of Fatigue During Static and Dynamic Exercise ; Summary -- Chapter 10. Endurance Training-Induced Adaptations in Substrate Turnover and Oxidation / Stuart M. Phillips, PhD ; Study Design Considerations ; Effect of Training on Substrate Turnover and Oxidation ; Underlying Mechanisms of Training-Induced Adaptations ; Summary.
Includes bibliographical references
Also available in print version
Keywords: Energy metabolism; Exercise -- Physiological aspects